Mycetoma caused by Nocardia brasiliensis in an immunocompetent patient - Sousa, Juliana M. P.; Wachholz, Patrick Alexander [UNESP]; Sette, Christiane S.; Marques, Gabriela F.; Barreto, Jaison A. (Wiley-Blackwell, 2014)
Dendritic cells play a central role in the regulation of immunological reactivity. The existence of functionally specialized populations of dendritic cells in the skin is a consequence of qualitatively different attacks on our organism. slanDCs are human inflammatory dendritic cells that are characterized by the specific expression of the carbohydrate 6-sulfo LacNAc (slan). After phenotypic maturation, slanDCs are capable of producing very high amounts of proinflammatory mediators such as IL-12, TNF-, IL-1 and IL-23. Recent data describe a potential role of slanDCs in a number of different diseases like psoriasis, lupus erythematosus, and tumors, thus opening up new areas of research on their respective pathogenesis. Furthermore, a slanDC-specific targeting system has been developed as a basis for direct therapeutic manipulation. Future challenges of slanDC research include deepening our understanding of the significance of slanDCs in the regulation of adaptive and innate immune responses, as well as translating this knowledge into therapeutic options.